Green wall systems: A review of their characteristics. (January 2015) - Manso, Maria; Castro-Gomes, João
Abstract: Current systems for greening the buildings envelope are not just surfaces covered with vegetation. Greening systems, as green roofs and green walls, are frequently used as an aesthetical feature in buildings. However, the current technology involved in these systems can maximize the functional benefits of plants to buildings performance and make part of a sustainable strategy of urban rehabilitation and buildings retrofitting. During the last decades several researches were conducted proving that green walls can contribute to enhance and restore the urban environment and improve buildings performance. The aim of this paper is to review all types of green wall systems in order to identify and systematize their main characteristics and technologies involved. So, it is important to understand the main differences between systems in terms of composition and construction methods. Most recent developments in green walls are mainly focused in systems design in order to achieve more efficient technical solutions and a better performance in all building phases. Yet, green wall systems must evolve to become more sustainable solutions. In fact, continuing to evaluate the contribution of recent green wall systems to improve buildings performance and comparing the environmental impact of these systems with other construction solutions can lead to an increase of their application in buildings and therefore result in a reduction on these systems cost. The decision of which green wall system is more appropriate to a certain project must depend not only on the construction and climatic restrictions but also on the environmental impact of its components and associated costs during its entire lifecycle.